The Intended and Unintended Effects of Promoting Labor Market Mobility - Marco Caliendo; Steffen Künn; Robert Mahlstedt (Institute of Labor Economics (IZA), 2022)
Subsidizing the geographical mobility of unemployed workers may improve welfare by relaxing their financial constraints and allowing them to find jobs in more prosperous regions. We exploit regional variation in the promotion of mobility programs along administrative borders of German employment agency districts to investigate the causal effect of offering such financial incentives on the job search behavior and labor market integration of unemployed workers. We show that promoting mobility - as intended - causes job seekers to increase their search radius, apply for and accept distant jobs. At the same time, local job search is reduced with adverse consequences for reemployment and earnings. These unintended negative effects are provoked by spatial search frictions. Overall, the unconditional provision of mobility programs harms the welfare of unemployed job seekers.
Keywords: J61; J68; D04; C21; 330; job search; active labor market policy; labor market mobility; unintended consequence; search frictions